Acetaminophen use and risk of renal impairment: A systematic review and meta-analysis - Sukrit Kanchanasurakit; Aimusa Arsu; Wuttikorn Siriplabpla; Acharaporn Duangjai; Surasak Saokaew (The Korean Society of Nephrology, 2020)
Background : : Acetaminophen is commonly used for the relief of pain and fever. Advocacy organizations recommend acetaminophen as the drug of choice in patients with kidney disease. Although some studies have suggested a risk of renal impairment after the use of acetaminophen, the effect of acetaminophen on the risk of renal impairment is unclear. The purpose of this research was to demonstrate any correlation linking acetaminophen treatment and renal impairment. Methods : : We performed a systematic review and meta-analysis of the association between acetaminophen and renal impairment in adults by searching Cochrane Library, PubMed, and Embase databases from initiation to June 16, 2019. Results : : Of 13,097 articles identified, 5 studies (2 cohort studies and 3 case-control studies) with a total of 13,114 participants were included. In the random-effects meta-analysis of the cohort study, acetaminophen use was shown to have statistically significant effects on the increased risk of renal impairment (adjusted odds ratio 1.23; 95% confidence interval, 1.07-1.40). The results of sensitivity and subgroup analyses also suggested that acetaminophen use increases the risk of renal impairment. The Egger's test (P = 0.607) and Begg's test (P = 0.732) revealed no apparent publication bias. Conclusion : : Acetaminophen is associated with a significantly increased risk of newly developing renal impairment in adults. Physicians who prescribe acetaminophen should be aware of potential adverse renal effects. A longitudinal study that further explores this association is warranted.